Comparison of approaches to reliability verification of existing steel structures - Nadolski, Vitali; Holicky, Milan; Sykora, Miroslav; Tur, Viktar (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
Many existing steel structures are exposed to degradation due to corrosion or fatigue and to increasing loads. Their reliability assessment is then needed. The key question is whether a particular structure can be preserved ‘as it is’, or needs to be strengthened, or whether it needs to be replaced. Unnecessary replacements of existing structures may be avoided and the remaining service life of existing steel structures may be authorized by: using advanced reliability verification techniques, optimizing target reliability, and obtaining data for a specific site or structure. In this contribution, the application of advanced reliability approaches is illustrated by the assessment of an existing steel structure. The case study demonstrates that such approaches may significantly improve assessment and allow to increase the load-bearing capacity of the structure (in the case under investigation by 10 to 20%). Improvements in reliability assessment are attributed to the use of an optimal target reliability level, case-specific statistical parameters and probabilistic distributions of the basic variables, and adjusted partial factors.